IMPLEMENTATION OF CONVERGENCE OF CROSS-SECTORAL ACTIVITIES IN HANDLING STUNTING - Askar Askar; Andi Nurul Abidah Ramli; Nawir Rahman; Risma Niswaty (Sosiohumaniora, 2023)
This study aims to determine the Implementation of Cross-Sectoral Activities Convergence Action in Stunting Handling in Sinjai district. This type of research uses qualitative research. Data collection techniques are carried out using interview techniques. Technical data validation. The data analysis technique used consists of data condensation, data presentation and conclusions. The results of this study show that in the Implementation of Cross-Sectoral Activities Convergence Action in Stunting Handling (Case Study: Sinjai Regency) seen from the implementation of public policy concepts, namely efforts to create relationships that allow policies to be realized such as Regent Regulation Number 10 of 2020 concerning Stunting Prevention and Handling in Villages and Regent Regulation Number 40 of 2021 concerning Stunting Prevention and Handling in Regions that  is a guide in the implementation of integrated stunting handling interventions and the existence of Regional Head committees as seen from the Decree of the Regent of Sinjai Number 363 of 2022 concerning the Formation of a Team for the Acceleration of Stunting Reduction in Sinjai Regency. Meanwhile, judging from the implementation of public policy in Sinjai Regency in terms of handling stunting, there are 6 dimensions of assessment. Of the six dimensions, there are 4 dimensions that are included in the good assessment, namely Inter-Organization Communication, Characteristics of the Implementing Organization, Economic, Social, and Political Conditions and Implementing Tendencies. While 2 dimensions are considered quite good, namely Standards, Objectives, Policies, and Resources. The conclusion of this study is that the implementation has been running but needs consistency in the future.